Getting in and getting on in the youth labour market governing young peoples employability in regional context - Leonard, Pauline 1957-; Wilde, Rachel J. ca. 20./21. Jh (Bristol shorts research, 2019)
Based on up to date qualitative and ethnographic research, this book examines youth education-to-work transitions in the UK. Using the theoretical lens of a Foucauldian governmentality approach, the authors consider the 'why' and 'how' of youth employability training and demonstrate how different employability schemes planned and operationalised in diverse geographical and economic landscapes work in practice. The book examines and compares a range of employment entry route programmes and reveals the tension between employability and good quality employment, and the ways in which young people from varying social and regional backgrounds are positioned very differently within this